Cross-Linguistic Interference: Errors in Learning English among Uzbek Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the phenomenon of interlingual interference in the context of English language acquisition by Uzbek students, providing an in-depth analysis of how the structure, rules, and usage patterns of the Uzbek language influence learners’ performance in English. Interlingual interference, also known as negative language transfer, refers to errors that occur when elements from a speaker’s native language interfere with the acquisition and use of a second language. This study focuses specifically on the types of mistakes commonly made by Uzbek learners of English at various proficiency levels, and it investigates the underlying linguistic causes of these errors. Through a detailed examination of written and spoken English samples produced by Uzbek students, the article identifies recurring patterns of grammatical, phonological, lexical, and syntactic errors. Particular attention is paid to issues such as incorrect verb tenses, omission of articles, subject-verb agreement mistakes, misused prepositions, and faulty sentence structures—all of which can be traced back to differences between Uzbek and English grammar systems. The research also sheds light on phonetic difficulties, including the substitution of English sounds with phonetically similar Uzbek ones, stress placement problems, and intonation errors that impact overall intelligibility and fluency. The article is grounded in a comparative linguistic framework, which allows for a contrastive analysis between Uzbek and English, revealing specific areas where interference is most likely to occur. It also incorporates insights from second language acquisition (SLA) theory, particularly the role of the learner's first language (L1) in shaping the learning process of a second language (L2). The study employs both qualitative and quantitative methods, including interviews with English teachers, classroom observations, and error analysis of student compositions and oral performances. One of the central aims of this research is to increase awareness among language instructors, curriculum designers, and educational policymakers about the unique challenges faced by Uzbek learners due to interlingual interference. The article emphasizes the importance of developing pedagogical strategies that explicitly address these interference-induced mistakes, such as contrastive grammar teaching, targeted pronunciation drills, and culturally responsive materials that bridge the linguistic gap between Uzbek and English. Furthermore, the article discusses the psychological and sociolinguistic dimensions of language interference, noting that learners’ confidence and motivation can be significantly affected by persistent errors. It argues that fostering metalinguistic awareness among students—encouraging them to consciously reflect on differences between languages—can reduce error rates and enhance overall language competence. In conclusion, the article contributes to the growing body of literature on L1 interference by providing empirical evidence and theoretical insights specific to the Uzbek-English language pair. It underscores the necessity of localized language instruction that takes into account the linguistic background of learners, and it proposes practical recommendations for improving English language teaching in Uzbekistan. Ultimately, the findings of this study aim to support more effective and equitable English language education by addressing the root causes of common learner errors through a nuanced understanding of interlingual interference.